ChemInform Abstract: Electrophilic Activation of Allenenes and Allenynes: Analogies and Differences Between Broensted and Lewis Acid Activation. Issue 26 (1st July 2014) - Caneque, T.; Truscott, F. M.; Rodriguez, R.; Maestri, G.; Malacria, M.
Abstract Review: 50 refs.